Efficacy and Safety of Xingnaojing Injection for Emergency Treatment of Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Wang, Liuding; Fan, Xueming; Chen, Yifan; Liang, Xiao; Shen, Wei; Zhang, Yunling (Frontiers in Pharmacology, 2022)
Background: Xingnaojing injection (XNJ) is derived from a traditional Chinese prescription named Angong Niuhuang pill. As an adjuvant treatment widely used in acute ischemic stroke (AIS), XNJ has proven to be effective with certain clinical evidence. The aim of this study is to collect the latest evidence and evaluate efficacy and safety of XNJ for emergency treatment of AIS. Methods:We searched seven literature databases and two clinical trial registries from their inception to November 14, 2021 for randomized controlled trials (RCTs) examining efficacy of XNJ for AIS. Two reviewers independently selected relevant trials, extracted data, and assessed the risk of bias. We pooled data into a meta-analysis using RevMan 5.4 software. Results:Thirty-eight RCTs were included in this review, with a total of 3677 participants. XNJ plus conventional treatments (CTs) showed a significant advantage, compared with CTs alone, in improving functional independence at 14 days (RR = 1.70, 95% CI = 1.03 to 2.81, P = 0.04), neurological function (MDNIHSS<6h = −3.81, 95% CI = −5.25 to −2.38, P < 0.00001; MDNIHSS<24h = −3.75, 95% CI = −4.92 to −2.59, P < 0.00001; MDNIHSS<72h = −3.74, 95% CI = −5.48 to −2.00, P < 0.0001; MDNIHSS<14d = −1.97, 95% CI = −3.25 to −0.69, P = 0.003), and activities of daily living on the Barthel index (MDBI-14day = 9.97, 95% CI = 9.29 to 10.65, P < 0.00001; MDBI-30day = 10.04, 95% CI = 5.82, to 14.26, P < 0.00001). In addition, results showed that XNJ plus CTs was superior to CTs alone in reducing IL-6, TNF-α, hs-CRP and MMP-9. Regarding safety of XNJ, the incidence of adverse reactions in the XNJ group was lower than that in the control group (RR = 0.57, 95% CI = 0.38 to 0.87, P = 0.009). Certainty of evidence was evaluated as low or very low for all. Conclusion: XNJ appears to be effective and safe for emergency treatment of AIS. The first 72 hours after the onset of stroke, in particular the first six hours, may be the optimum initiation time. However, further high-quality RCTs are warranted to determine an appropriate initiation time.